RASGRF2 gene fusions identified in a variety of melanocytic lesions with distinct morphological features. (23rd August 2021) - Houlier, Aurélie; Pissaloux, Daniel; Tirode, Franck; Lopez Ramirez, Noémie; Plaschka, Maud; Caramel, Julie; Masse, Ingrid; de la Fouchardiere, Arnaud
Abstract: The WHO classification identifies nine classes of melanocytic proliferations according to location, UV exposure, histological, and genetic features. Only a minority of lesions remain unclassified. We describe five cases that harbored either an ERBIN‐RASGRF2 or an ATP2B4‐RASGRF2 in‐frame fusion transcript. These lesions were collected from different studies, unified only by the lack of identifiable known mutations, with a highly variable phenotype. One case was a large abdominal congenital nevus, three were slowly growing pigmented nodules, and the last was an ulcerated nodule arising on the site of a preexisting small nevus, known since childhood. The latter was diagnosed as a 4 mm thick melanoma with loss of BAP1 expression. The four other cases were compound, melanocytic proliferations with an unusual deep pattern of small dense nests of bland melanocytes encased in a fibrous background. The RASGRF2 fusion was confirmed by a break‐apart FISH technique. Array CGH performed in three cases found non‐recurrent secondary copy number alterations. Follow‐up was uneventful. In silico analysis identified a single RASGRF2 fusion in the TCGA pan‐cancer database, whereas RASGRF2 variants were stochastically distributed in all cancer subtypes.